2004
DOI: 10.1117/1.1695408
|View full text |Cite
|
Sign up to set email alerts
|

Intermodulation product effects on the working of a phased-array transducer acousto-optic switch

Abstract: Acousto-optic devices play an important role in the field of optical information and communication. For a few years, we have worked on acousto-optic deflection in the Bragg regime at 1.55-m wavelength, by controlling the rf signal applied to the piezoelectric transducer. Recently, still using the acousto-optic interaction, we have taken an interest in the 2ϫ2 switching function. We present an acousto-optic switch architecture based on phased-array transducers. In the same crystal, we superimpose two diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…23 It was found that in the mode of the phase modulation index 3 γ π = there is an increase in the efficiency of the AOD. 24 The maxima of diffraction efficiency, as a function of sound power, are observed at: To eliminate the influence of thermal effects in AOD measurements were carried out in pulse mode -the duty cycle is 20. Figure 10 shows the experimental dependences of the maximum efficiency of diffraction of the frequency of the ultrasound.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 It was found that in the mode of the phase modulation index 3 γ π = there is an increase in the efficiency of the AOD. 24 The maxima of diffraction efficiency, as a function of sound power, are observed at: To eliminate the influence of thermal effects in AOD measurements were carried out in pulse mode -the duty cycle is 20. Figure 10 shows the experimental dependences of the maximum efficiency of diffraction of the frequency of the ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…Various methods of controlling this phase shift are known: anti-phase inclusion of neighboring elements, installation of elements on "steps", carved in the crystal in which the interaction occurs, 6 by shifting the phases of the control electrical signals of the multielement Converter. 24,25 However, these solutions are quite technically complex. In 26 shows the possibility of expanding the scanning range of AOD using only two-element piezoelectric transducer Figure 12.…”
Section: Deflector With Two-element Phased Array Piezoelectric Transd...mentioning
confidence: 99%
“…For a few years, we have worked on the development of a 2×2 switch based on an acousto-optic Bragg cell for telecommunication applications [7,8,9]. The Bragg cell is made of piezoelectric phased array transducers bonded to a crystalline material.…”
Section: Introductionmentioning
confidence: 99%
“…These include realizations based on optical MEMS [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], thermal optical [33][34][35], semiconductor optic amplifiers (SOA) [36], liquid crystals [37], electro-holography [38], electro-optical LiNb03 [39], electronically waveguide Bragg grating [9], acousto-optical [40][41][42][43] and opto-optical switches [44][45][46][47][48][49], respectively.…”
Section: Types Of Optical Switchesmentioning
confidence: 99%